2015
DOI: 10.1186/s13567-015-0252-6
|View full text |Cite
|
Sign up to set email alerts
|

Free exopolysaccharide from Mycoplasma mycoides subsp. mycoides possesses anti-inflammatory properties

Abstract: In this study we explored the immunomodulatory properties of highly purified free galactan, the soluble exopolysaccharide secreted by Mycoplasma mycoides subsp. mycoides (Mmm). Galactan was shown to bind to TLR2 but not TLR4 using HEK293 reporter cells and to induce the production of the anti-inflammatory cytokine IL-10 in bovine macrophages, whereas low IL-12p40 and no TNF-α, both pro-inflammatory cytokines, were induced in these cells. In addition, pre-treatment of macrophages with galactan substantially red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 45 publications
0
22
0
1
Order By: Relevance
“…Galactan was shown to protect M. mycoides subsp. mycoides from serum killing when cell attached (15) and to possess anti-inflammatory properties when secreted as an exopolysaccharide (14). We have demonstrated here that M. agalactiae strains producing ␤-(1¡6)-glucan in contact with goat sera or the complement fraction of guinea pig sera were rapidly killed, suggesting that they might be rapidly eliminated from the bloodstream of infected animals, prior to the acquisition of antimycoplasma immunity.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Galactan was shown to protect M. mycoides subsp. mycoides from serum killing when cell attached (15) and to possess anti-inflammatory properties when secreted as an exopolysaccharide (14). We have demonstrated here that M. agalactiae strains producing ␤-(1¡6)-glucan in contact with goat sera or the complement fraction of guinea pig sera were rapidly killed, suggesting that they might be rapidly eliminated from the bloodstream of infected animals, prior to the acquisition of antimycoplasma immunity.…”
mentioning
confidence: 79%
“…The role of ␤-(1¡2)-glucan has not yet been studied, but the galactan in M. mycoides subsp. mycoides strain Afadé has been found both to exhibit anti-inflammatory properties in EPS form (14) and to protect the cells from the bactericidal activity of the serum when in CPS form (15).…”
mentioning
confidence: 99%
“…Despite lacking a cell wall, some mycoplasma can produce capsular polysaccharides and/or exopolysaccharides (Neyrolles et al, 1998; Daubenspeck et al, 2009; Bertin et al, 2013, 2015; Simmons et al, 2013; Gaurivaud et al, 2016). Among these identified polysaccharides, some carbohydrate components have been characterized to have anti-inflammatory effects and contribute to biofilms formation (Totté et al, 2015). At the moment, few studies have been carried out regarding capsular polysaccharides and/or exopolysaccharides or their influence on the host during the process of mycoplasma infection, such as their participation in cell adhesion or anti-phagocytosis effects.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Based on in vitro experiments, it has been suggested that the Mycoplasma gallisepticum capsule is involved in adhesion and virulence [2], the exopolysaccharides of Mycoplasma pulmonis protect against the complement system [3], CPS of Mycoplasma dispar down-regulates macrophage function [4], and purified CPS of Mycoplasma ovipneumoniae induces an inflammatory response through Toll-like receptor signaling in airway epithelial cells [5]. The exopolysaccharides of members of the “ Mycoplasma mycoides cluster” have been characterized [6] and free CPS of M. mycoides induces the production of interleukin 10 in bovine macrophages, which acts as an anti-inflammatory [7].…”
mentioning
confidence: 99%